PENDAMPINGAN PENGISIAN FORMAT PEMBUKUAN DANA DESA KOMPANG KECAMATAN SINJAI TENGAH KABUPATEN SINJAI - Ni'mah, Siar; Lestari, Ririn; Umar, Umar (LPPM Universitas Pamulang, 2024)
Filling in the bookkeeping format is a process of recording financial transactions into accounting records. The transaction in question includes recording and bookkeeping which is also carried out in an effort to find out the financial position of the results of business activities. The assistance in completing the bookkeeping format aims to provide knowledge, understanding and skills to executors of financial management/village treasurers in making simple bookkeeping, as well as assisting in implementing bookkeeping in daily activities. The results of this activity will help financial managers better understand the process of making financial reports and the importance of bookkeeping. The method used is in the form of assistance in filling out the Village Fund Bookkeeping Format. The results of this activity indicate that cash assistance can facilitate the recording of transactions made in Kompang Village.